A Review of the Parametric Characteristics of Urban Environment and it's Influence to the Urban Quality of Life. (2018) - Eusuf, Muhammad Abu; RSE, Muhammad Saadmann; RSE, Muhammad Mehbub; Ibrahim, Mansor
No abstract available